Kansas State University Swine Enterprise Record summary - Richert, B.T.; Langemeier, Michael R.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Approximately 30 swine operations are enrolled in the 1992 - 93 Kansas Swine Enterprise Record Program provided by Kansas State University. This program evaluates biological and economic performance and is part of a cooperative record-keeping project with extension personnel and swine producers in Kansas, Nebraska, and South Dakota. Records are summarized every 6 months, and the corresponding data are pooled to form state and regional averages. This summary is the combined data for the 18 farrow-to-finish operations in Kansas that kept records during 1992. The semiannual data represents the last 6 months of 1992, whereas the annual data are for the 12-month period of January 1, 1992 to December 31, 1992. Profit per cwt of pork produced for these 18 producers averaged a loss of 4.78 for the last 6 months and a loss of $.52 for the entire year. Profits varied substantially between producers. Producers in the top one-third in terms of profitability had average profits of $5.72 per cwt, whereas producers in the bottom one-third had average losses of $6.97 per cwt for the year. Critical factors separating low- and high-profit producers included feed costs, unpaid labor, fixed costs, and sow productivity.
Typo of author's name M. L. Langemeier; should be M. R. Langemeier.
Keywords: Swine; Enterprise; Records; Analysis; Profitability